SOG‘LOM TURMUSH TARZINI YAXSHILASHDA ATROF-MUHITNING O‘RNI - Beknazarovich, Ernazarov Abduvali (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Maintaining a healthy lifestyle and living a long life requires an active lifestyle and regular physical exercise, which are of great importance. Method: In ensuring a healthy lifestyle, proper nutrition plays a key role, and it is also necessary to strictly adhere to hygiene requirements during the eating process. Results: Improving a healthy lifestyle also depends on the cleanliness and protection of the environment, which is crucial. Novelty: The Zoroastrian religion's